Inversion-derived VD-MLI interlayer pressure prediction based on gas transport mechanisms - wu, Hao; Tan, Hongbo; Xu, Zhangliang (International journal of hydrogen energy, 2025)
In ground-based liquid hydrogen storage and transportation systems, the interlayer pressure within Multilayer Insulation (MLI) exhibits a non-uniform distribution. This is primarily attributed to the combined effects of flow resistance, material outgassing, and cryo-adsorption. Consequently, the interlayer pressure is often significantly higher than the pressure within the vacuum chamber. A clear understanding of the gas transport mechanisms within the interlayers of MLI is critical for enhancing the vacuum lifetime of liquid hydrogen storage tanks and reducing their manufacturing costs. This study developed a gas transport equation for MLI that incorporates both interlayer adsorption effects and variable density factors. By solving a Layer-By-Layer (LBL) model, a dataset of interlayer pressure-temperature samples was established through simulation. Subsequently, interlayer pressure was inversely determined from measured interlayer temperatures, utilizing this sample dataset to address the issue of missing boundary conditions in the governing equations for interlayer gas dynamics. Investigations conducted using a liquid hydrogen calorimeter tested two Variable Density MLI (VD-MLI) configurations. The inversion results revealed that with an increase in the porosity of the reflective shields, the interlayer pressure distribution transitioned from an “L”-shape towards a linear profile. The peak interlayer pressures were found to be 43.43 and 17.71 times the chamber pressure, respectively. The heat flux densities corresponding to the inverse solutions for these two VD-MLI configurations deviated from the experimental results by 13.3 % and 8.7 %, respectively. The interlayer gas transport equation and inversion algorithm proposed in this study enable the efficient and accurate determination of interlayer pressure distribution within VD-MLI. This provides a methodological breakthrough and essential technical tools to support the insulation design, vacuum longevity prediction, and reliability enhancement of liquid hydrogen storage and transportation systems. •A novel gas transport equation for VD-MLI is developed, coupling cryo-adsorption and layer density effects.•A TSVD-LSQR based inversion method is proposed to determine interlayer pressure with ill-defined boundary conditions.•Increased porosity is experimentally proven to transition the interlayer pressure profile from “∩“-shaped to “L”-shaped.